Siblings, shopping, and sustainability: Birth-order differences in green consumption - Otterbring, Tobias; Sundgot-Borgen, Christine; Bratland-Sanda, Solfrid; Trangsrud, Lise Katrine Jepsen (Frontiers in Psychology, 2023)
Several studies have examined the role of birth order in shaping human personality, but fewer have tested this variable in relation to other pressing issues. We conducted a birth-order study on green consumption, which enabled us to detect a small-to-moderate effect size equivalent to r = .15 or d = 0.30 with sufficient statistical power (N = 335). To capture green consumption, participants indicated their tendency to express the value of environmental protection through purchases and consumption behaviors. Firstborns (vs. laterborns) consistently expressed lower concerns linked to environmental protection in their purchase patterns. While the effect size of this finding was small-to-moderate by conventional standards and in direct contrast to the findings from a recent article on the same topic, these results could still be informative to address challenges associated with climate change considering the number of individuals with siblings in the world and the ease with which birth-order data can be collected.